Comparison of gingivectomy procedures for patient satisfaction: Conventional and diode laser surgery - Elif Öncü (Selçuk University, 2017)
Background: To compare the use of the 940 nm diode laser with conventional surgery in the management of soft tissue in gingivectomy procedures in terms of patient satisfaction.Methods: This controlled clinical trial was conducted on 20 healthy patients who needing esthetic-only gingivectomy in the anterior maxilla. The patients were randomly divided into two groups of 10 each: experimental (diode laser-assisted surgery) and control (traditional surgery using scalpels). The bleeding rate following the surgery was assessed using the bleeding criteria established by the World Health Organization. The postsurgical discomfort level was recorded using visual analog scales (VAS), surgery time was evaluated for each operation and postoperative analgesic requirements were evaluated and compared.Results: In control groups, anesthesia requirements were found statistically higher during surgery (p<0.001). The average bleeding rates were 1.32 and 0.24 in the conventional and laser groups, respectively (p<0.001). Experimental patients had no postsurgical pain but in the control group, VAS pain level was found higher. The difference between VAS values in each groups were significant (p<0.001). There was no significant difference for surgery time between the treatment type.Conclusion: This study shows that the diode laser has a great advantage over conventional surgery in the gingivectomy procedures.